Australian sponge barnacles: diversity, host dynamics and systematics - Hosie, Andrew M. (Curtin University, 2021)
This study applied molecular phylogenetic tools to examine the evolutionary history of barnacles symbiotic with sponges. The transition from free-living to sponge-symbiosis has evolved independently at least three times within this group. The evolution of sponge symbiosis resulted in significant adaptive radiation, and over 100 species were identified, including >50 new species, from Australian waters. Host use was typically restricted to a few species and phylogenetically conserved.